2005
DOI: 10.1111/j.1365-2044.2004.04076.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite‐induced methaemoglobinaemia – aetiology, diagnosis and treatment

Abstract: SummaryA 41-year-old woman presented with the clinical features of methaemoglobinaemia after drinking Chinese herbal medicine. A life threatening methaemoglobin level of 68% was measured. Both clinical and laboratory diagnostic difficulties were encountered. The pitfalls of pulse oximeter, blood gas analysis and co-oximeter interpretation during diagnosis and after methylene blue administration are discussed. Methaemoglobinaemia is an unusual and potentially fatal condition in which haemoglobin is oxidised to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 11 publications
(9 reference statements)
1
47
0
3
Order By: Relevance
“…Although methemoglobinemia due to AlP intoxication has been reported only in one case [7], the present study showed that there is a significant association between blood level of Met-Hb and mortality in AlP intoxication cases. Clinical manifestations of methemoglobinemia are due to decreased O 2 -carrying capacity of hemoglobin and consequent tissue hypoxia [13]. We believe that in patients suffering from AlP intoxication, death occurs mainly due to other more serious complications such as hypotension and shock rather than methemoglobinemia.…”
Section: Discussionmentioning
confidence: 92%
“…Although methemoglobinemia due to AlP intoxication has been reported only in one case [7], the present study showed that there is a significant association between blood level of Met-Hb and mortality in AlP intoxication cases. Clinical manifestations of methemoglobinemia are due to decreased O 2 -carrying capacity of hemoglobin and consequent tissue hypoxia [13]. We believe that in patients suffering from AlP intoxication, death occurs mainly due to other more serious complications such as hypotension and shock rather than methemoglobinemia.…”
Section: Discussionmentioning
confidence: 92%
“…61 However, nitrite can also be harmful to mammals, as it can oxidize ferrous hemoglobin (Hb) and increase the in vivo levels of ferric Hb to result in the blood disorder methemoglobinemia. 62,63 …”
Section: Nitrite Linkage Isomersmentioning
confidence: 99%
“…Accidental or intentional acute exposure to high levels of nitrite has been reported to cause death, mainly due to methemoglobinemia [8,9]. Chronic exposure to lower doses of nitrite causes adverse health effects, which includes birth defects, respiratory tract ailments, damage to the nervous system and paralysis [10].…”
Section: Introductionmentioning
confidence: 99%